Wealth effects in emerging market economies - Tuomas A. Peltonen; Ricardo M. Sousa; Isabel Vansteenkiste (European Central Bank (ECB), 2009)
We build a panel of 14 emerging economies to estimate the magnitude of housing, stock market, and money wealth effects on consumption. Using modern panel data econometric techniques and quarterly data for the period 1990:1-2008:2, we show that: (i) wealth effects are statistically significant and relatively large in magnitude; (ii) housing wealth effects tend to be smaller for Asian emerging markets while stock market wealth effects are, in general, smaller for Latin American countries; (iii) housing wealth effects have increased for Asian coutries in recent years; and (iv) consumption reacts stronger to negative than to positive shocks in housing and financial wealth.
Keywords: E21; E44; D12; 330; Consumption; emerging markets; wealth eects; Vermögenseffekt; Privater Konsum; Schwellenländer; Welt